2007
DOI: 10.1039/b707465d
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic oxidation of methanol on Pd metal and oxide clusters at near-ambient temperatures

Abstract: Supported Pd clusters catalyze methanol oxidation to methyl formate with high turnover rates and >90% selectivity at near ambient temperatures (313 K). Metal clusters are much more reactive than PdO clusters and rates are inhibited by the reactant O(2). These data suggest that ensembles of Pd metal atoms on surfaces nearly saturated with chemisorbed oxygen are required for kinetically-relevant C-H bond activation in chemisorbed methoxide intermediates. Pd metal surfaces become more reactive with increasing met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 41 publications
5
58
1
1
Order By: Relevance
“…Formyl species have also been found at this temperature, but they promptly disappear if the catalyst is heated and the formation of CO and H 2 prevails 28. 30 Methyl formate can be formed through the condensation of adsorbed methoxides with HCHO to form methoxymethanol intermediates, which then dehydrogenate to methyl formate 31. The esterification of formic acid intermediates formed by HCHO oxidation is also possible, but the high selectivities to methyl formate reported here indicate that fast reactions occur through condensation of HCHO to methyl formate.…”
Section: Discussionmentioning
confidence: 99%
“…Formyl species have also been found at this temperature, but they promptly disappear if the catalyst is heated and the formation of CO and H 2 prevails 28. 30 Methyl formate can be formed through the condensation of adsorbed methoxides with HCHO to form methoxymethanol intermediates, which then dehydrogenate to methyl formate 31. The esterification of formic acid intermediates formed by HCHO oxidation is also possible, but the high selectivities to methyl formate reported here indicate that fast reactions occur through condensation of HCHO to methyl formate.…”
Section: Discussionmentioning
confidence: 99%
“…[13,15] Methyl formate can form through the condensation of adsorbed methoxides with HCHO to form methoxymethanol intermediates (CH 3 OCH 2 OH) that then dehydrogenate to methyl formate. [16] The esterification of formic acid (HCOOH) intermediates formed by HCHO oxidation is also possible but the high selectivities to methyl formate reported here indicate that fast reactions through condensation of HCHO to methyl formate occur. However, works using DRIFT in operando mode are presently in progress to understand the mechanism of methyl formate formation.…”
mentioning
confidence: 89%
“…Except for noble‐metal‐based catalysts, the aforementioned oxides perform modestly in the reaction . The performance of noble metals has been related to their reducibility . Lichtenberger et al .…”
Section: Introductionmentioning
confidence: 99%
“…The performance of noble metals has been related to their reducibility . Lichtenberger et al . showed that reduced palladium species perform better in the reaction than oxidized PdO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation